2000
DOI: 10.1159/000010215
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraoperative Frozen-Section Diagnosis in Stage I Endometrial Adenocarcinoma

Abstract: The purpose of our study was to determine if frozen-section diagnosis accurately identified patients suffering from endometrial adenocarcinoma FIGO stage I for surgical staging consisting of total abdominal hysterectomy, bilateral salpingo-oophorectomy, peritoneal cytology, and complete bilateral pelvic lymphadenectomy in moderately differentiated tumors with myometrial invasion. In all poorly differentiated tumors, and in all tumors with deep myometrial invasion (more than 50%) surgical staging included addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 14 publications
(25 reference statements)
2
47
0
1
Order By: Relevance
“…The accuracy rate of grade that is detected with probe curettage in accordance with the results of paraffin blocks ranges between 36%-96% (2,(23)(24)(25). Intraoperatively, grade could be defined with an accuracy of 58%-98%; with FS, according to postoperative pathology, these rates for DMI and cervical invasion are 54%-95% and 95%, respectively (26)(27)(28)(29)(30)(31)(32)(33)(34). In contrast, others argue that FS could not predict lymphatic spread well, meaning that all patients with endometrium cancer should be staged systematically (27).…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy rate of grade that is detected with probe curettage in accordance with the results of paraffin blocks ranges between 36%-96% (2,(23)(24)(25). Intraoperatively, grade could be defined with an accuracy of 58%-98%; with FS, according to postoperative pathology, these rates for DMI and cervical invasion are 54%-95% and 95%, respectively (26)(27)(28)(29)(30)(31)(32)(33)(34). In contrast, others argue that FS could not predict lymphatic spread well, meaning that all patients with endometrium cancer should be staged systematically (27).…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative evaluation of the hysterectomy specimen by frozen-section in women with endometrioid type endometrial cancer has been shown to successfully reveal tumor characteristics including grade, size and depth of myometrial invasion. The extent of surgery may be decided accordingly (15,16). The same principle may be adapted into the surgical management of patients with EIn.…”
Section: Discussionmentioning
confidence: 99%
“…A decision to proceed with staging at the time of surgery depends on the presence and depth of myometrial invasion, the grade of disease, and the diameter of the tumor (14). Frozen-section examination was used in several studies to accurately reveal such tumor characteristics and therefore guide the extent of surgery in patients with endometrioid type endometrial carcinoma (15,16). However, very little data exists in the literature regarding the performance of intraoperative frozen-section consultation in women with endometrial precancers (4).…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] Routine MRI scanning of all patients with AEH to identify those patients with deep myometrial invasion would have such a low yield that it would not be cost-effective. In our review, only 6% of patients would have benefited from such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Concurrent use of frozen section analysis can further enhance intraoperative risk determination in patients with endometrial cancer. [31][32][33][34] However, in a review of 23 patients, only four of 11 patients found to have concurrent EC were identified by frozen section assessment. 31 The limitations of our study arise from the relatively small number of patients and the retrospective collection of data.…”
Section: Discussionmentioning
confidence: 99%